2019
DOI: 10.1021/acsami.8b22159
|View full text |Cite
|
Sign up to set email alerts
|

CO2-Responsive Cellulose Nanofibers Aerogels for Switchable Oil–Water Separation

Abstract: Cellulose nanofibers (CNFs) aerogels with controllable surface wettability were prepared by grafting poly(N,N-dimethylamino-2ethyl methacrylate) (PDMAEMA) polymer brushes via surface-initiated atom-transfer radical polymerization. After grafting PDMAEMA polymer, the surface of the aerogel was hydrophobic. However, in the presence of CO 2 , the surface of the aerogel gradually changes from hydrophobic to hydrophilic. The porous structure and CO 2 -responsiveness of PDMAE-MA brushes within the CNFs aerogels allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
98
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(98 citation statements)
references
References 38 publications
(64 reference statements)
0
98
0
Order By: Relevance
“…For example, Sui et al reported a switchable, CO 2 ‐responsive oil–water separation material based on aerogels of cellulose nanofibers. The material was prepared by grafting poly( N , N ‐dimethylamino‐2‐ethyl methacrylate) (PDMAEMA) polymer brushes via surface‐initiated atom‐transfer radical polymerization . Bai et al reported a superhydrophilic and underwater superoleophobic membrane for oil/water emulsion separation based on the in situ crosslinking copolymerization of polyethyleneimine (PEI) and poly(methyl methacrylate‐ co ‐glycidyl methacrylate) P(MMA‐ co ‐GMA) on poly(vinylidene fluoride) (PVDF) membrane .…”
Section: Surface Modification Of the Micro‐/nanostructurementioning
confidence: 99%
See 1 more Smart Citation
“…For example, Sui et al reported a switchable, CO 2 ‐responsive oil–water separation material based on aerogels of cellulose nanofibers. The material was prepared by grafting poly( N , N ‐dimethylamino‐2‐ethyl methacrylate) (PDMAEMA) polymer brushes via surface‐initiated atom‐transfer radical polymerization . Bai et al reported a superhydrophilic and underwater superoleophobic membrane for oil/water emulsion separation based on the in situ crosslinking copolymerization of polyethyleneimine (PEI) and poly(methyl methacrylate‐ co ‐glycidyl methacrylate) P(MMA‐ co ‐GMA) on poly(vinylidene fluoride) (PVDF) membrane .…”
Section: Surface Modification Of the Micro‐/nanostructurementioning
confidence: 99%
“…The material was prepared by grafting poly(N,Ndimethylamino-2-ethyl methacrylate) (PDMAEMA) polymer brushes via surface-initiated atom-transfer radical polymerization. [128] Bai et al reported a superhydrophilic and underwater superoleophobic membrane for oil/water emulsion separation based on the in situ crosslinking copolymerization of polyethyleneimine (PEI) and poly(methyl methacrylate-co-glycidyl methacrylate) P(MMA-co-GMA) on poly(vinylidene fluoride) (PVDF) membrane. [129] Wu et al reported a superhydrophobic cotton fabric via radiation-induced graft polymerization of γ-methacry loxypropyltrimethoxy silane (MAPS) and subsequently end-capping modification with hexamethyldisilazane (HMDS).…”
Section: Chemical Modificationmentioning
confidence: 99%
“…Although these systems are capable of demonstrating remarkable separation efficiencies, the extreme pH required does leave room for milder triggers. For example, Li et al impart CO 2 ‐response in poly( N , N ‐dimethylamino‐2‐ethyl methacrylate) grafted cellulose nanofiber aerogels to effect the desired pH change . The decrease in pH upon bubbling through CO 2 results in protonation of the dimethylamino functional groups at the membrane surface, leading to a changeover in oil–water separation over 50 s as the water contact angle recedes from 130° to 0°.…”
Section: Responsive Permeabilitymentioning
confidence: 99%
“…CO 2 ‐responisve polymers were already grafted on cellulose in different reports . However, the purpose of those grafted CNCs was mainly for applications using gas‐responsive CNCs as Pickering emulsifier or membrane for oil–water separation.…”
mentioning
confidence: 99%
“…[19] CO 2 -responisve polymers were already grafted on cellulose in different reports. [4,18,[20][21][22] However, the purpose of those grafted CNCs was mainly for applications using gas-responsive CNCs as Pickering emulsifier or membrane for oil-water separation. In the present work, we demonstrate a novel application by using gas-responsive CNCs to solve the challenging issue of compatibility when using CNCs as a reinforcing agent in both hydrophilic and hydrophobic polymer matrices for nanocomposite materials.…”
mentioning
confidence: 99%